Analisis Dampak Pertumbuhan Ekonomi, Indeks Pembangunan Manusia dan Pengangguran Terhadap Tingkat Kemiskinan Pada Kabupaten /Kota di Jawa Timur - Imamah, Nurul (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
Poverty is multi-dimensional concept of human welfare that includes many traditional measures of prosperity. Economic growth and health issues are the primary condition for poverty reduction in the region. The object of this study is how the results of estimates and projections of the poverty level. In this study also discusses the factors that affect poverty, namely the economic growth, Human Development Index, the Unemployment Rate and discuss how they affect poverty levels. This study aimed to analyze the factors affecting the level of poverty. This study used panel data regression analysis. This use to analyze the influence of economic growth, Human Development Index and Unemployment against Poverty Level.With the study period from 2011 - 2015. In each of the projections will be analyzed how the Poverty Level 38 City / Regency East Java province in Indonesia until 2015 formed.Results of analysis using panel data regression is known that variable economic growth, Human Development Index and Unemployment rate significantly affect the level of poverty. It shows that in all three of these variables has an inverse relationship to the level of poverty.